Estimating maternal mortality and identifying causes of maternal deaths in Jammu and Kashmir: a two-year epidemiological study - Rehman, Saleem Ur; Jeelani, Asif; Luthra, Anup (International Journal of Advances in Medicine, 2023)
Background: An accurate estimate of the maternal mortality ratio and its underlying causes is crucial for the effective planning of maternal health services. The aim of the study was to estimate the maternal mortality ratio (MMR) and identify causes of maternal deaths in Jammu and Kashmir. A subnational geographical area in India. Methods: The study included maternal deaths from April 2020 to March 2022 among residents of Jammu and Kashmir. We enumerated all maternal deaths and recorded their socio-clinical parameters from interviews with family members. The cause of death was inferred from the medical records and verbal autopsy. Live births data for the corresponding period was obtained from the routine health management information system. We calculated the maternal mortality ratio using a standard formula. Results: A total of 185 maternal deaths and 3.97 lakh live births were recorded over the two-year study period. It translated into an MMR of 47 per lakh live births, exhibiting noteworthy variability between districts. Postpartum haemorrhage (PPH) and hypertensive disorders of pregnancy accounted for a substantial proportion of maternal deaths, representing 44.3% (82/185) of cases. Sepsis and other obstetric complications were identified as the cause of death in 15.7% (29/185) and 19.5% (36/185) of maternal deaths, respectively. Furthermore, the majority of maternal deaths occurred among women between 25-30 years of age. Approximately two-thirds of maternal deaths occurred during the post-partum period. Conclusions: In summary, our study reveals that the maternal mortality rate (MMR) in Jammu and Kashmir falls below the sustainable development goal target, albeit with marked inter-district variability pointing to disparities in healthcare delivery. We recommend expanding the coverage of evidence-based interventions aimed at reducing the incidence of postpartum haemorrhage, eclampsia, and other obstetric complications to improve maternal health outcomes.